2016
DOI: 10.1093/pubmed/fdw069
|View full text |Cite
|
Sign up to set email alerts
|

Differences in substance use between sexual orientations in a multi-country sample: findings from the Global Drug Survey 2015

Abstract: Higher rates of substance use in bisexuals compared with homosexuals among both genders and larger differences between female groups highlight the importance of differentiating between sexual minority identities in substance use research, and in designing substance misuse interventions for people with a sexual minority identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 26 publications
6
61
1
1
Order By: Relevance
“…Participants in this sample have reported high levels of lifetime and recent poppers use. This is consistent with the current body of evidence demonstrating higher levels of poppers use in sexual minority men; however, most literature reports even higher levels of poppers use in this population .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Participants in this sample have reported high levels of lifetime and recent poppers use. This is consistent with the current body of evidence demonstrating higher levels of poppers use in sexual minority men; however, most literature reports even higher levels of poppers use in this population .…”
Section: Discussionsupporting
confidence: 90%
“…While poppers are used by populations of all sexual identities, research has shown that gay and bisexual men are disproportionately more likely to use these. A recent international survey reported that, in comparison to heterosexual men, those identifying as gay or bisexual had adjusted odds ratios of lifetime poppers use of 5.1 and 1.88, respectively. Last month use was also significantly higher with 1.5% among heterosexual men compared to 16.2% and 4.5% among gay and bisexual men, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…SMs are more likely to have an alcohol use disorder (AUD) and experience greater AUD severity (Allen and Mowbray, 2016; Amadio, 2006; McCabe et al, 2009). Notably, while heterosexual women have significantly lower rates of substance use than heterosexual men, SM women have similar or higher rates of substance use behaviors and disorders compared to SM men (Demant et al, 2017; Kerridge et al, 2017; McCabe et al, 2013; Operario et al, 2015). …”
Section: Introductionmentioning
confidence: 98%
“…A meta-analysis of 18 school-based surveys reported that US SM youth had nearly three times the odds of any substance use relative to heterosexual youth, smoking rates 2–3 times higher those of heterosexuals and approximately 1.5 times the odds of marijuana use (Marshal et al, 2008). These disparities persist in adulthood: in national surveys in the US and Canada, SM adults report more alcohol use and heavy episodic drinking (HED) than heterosexual adults (Allen and Mowbray, 2016; McCabe et al, 2009; Pakula et al, 2016), and national surveys in the US and Australia have found SM adults to have significantly elevated marijuana use (Demant et al, 2017; McCabe et al, 2009). Similarly, national surveys find SM youth and adults have elevated cigarette smoking rates and higher odds of moderate or heavy smoking, especially women (Cochran et al, 2013; Corliss et al, 2014; Gonzales et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation